DEVELOPMENT OF NATURAL FIBER HONEYCOMB STRUCTURE USING INJECTION MOLDING - AZIZI, AZRI (2018)
This paper is focused on the development of honeycomb cores manufactured through injection molding by combining rice husk fibers and polypropylene. The honeycomb structure is manufactured using a ready-made honeycomb mold. The materials used which is a composition of rice husk and polypropylene was tested through Thermogravimetric Analysis in order to check for the accuracy of the composition. Once the honeycomb structures was fabricated, its physical and mechanical properties was evaluated through the dimensional accuracy of the honeycomb core produced and a compressive test. The physical test conducted through the measurement of the honeycomb structure found that there is slight variations to the dimensions of the honeycomb core which is mainly due to the honeycomb mold and not the material composition. As of the compressive test, it is found that the compressive strength of the structures are directly proportional to the rice husk composition. Lastly, a new honeycomb mold was designed and evaluated to produce more honeycomb structures for future tests.